1980
DOI: 10.1083/jcb.87.2.404
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of motility in the microtubular axostyle: implications for cytoplasmic microtubule structure and function.

Abstract: The gross morphology of the protozoan microtubule axostyle of Saccinobaculus ambloaxostylus can now be described in macromolecular detail. The left-handed coil of the axostyle is seen to be dependent upon the asymmetry inherent in the constituent microtubules as expressed by the specific array of linkages between microtubules and by a possible tendency for microtubules to coil into left-handed helices. The laminated sheets of microtubules are not aligned parallel to the long axis of the organelle, but become i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…Successful reactivation has generally been obtained only when detergent extraction and ATP exposure are performed in rapid succession directly on the microscope stage, without washing away soluble cellular contents or subjecting axostyles to centrifugation (2,29,40). In fact, the only axostyles in our preparations that show rhythmic, propagated activation upon exposure to ATP are ones that attach to the glass slide during viewing; these happen to retain their nucleus and other cytoplasmic components.…”
Section: Phase-contrast Microscopy Of Living Organisms Vs Reactivatementioning
confidence: 99%
See 3 more Smart Citations
“…Successful reactivation has generally been obtained only when detergent extraction and ATP exposure are performed in rapid succession directly on the microscope stage, without washing away soluble cellular contents or subjecting axostyles to centrifugation (2,29,40). In fact, the only axostyles in our preparations that show rhythmic, propagated activation upon exposure to ATP are ones that attach to the glass slide during viewing; these happen to retain their nucleus and other cytoplasmic components.…”
Section: Phase-contrast Microscopy Of Living Organisms Vs Reactivatementioning
confidence: 99%
“…This somehow generates bends perpendicular to the long axis of the whole ribbon (3, 8, 17, 24-26, 29, 34), and because the axostyle is permanently twisted along its length, it also involves a change in helical pitch. Additionally, the bends propagate from one end of the axostyle to the other, causing the organelle to rotate inside the cell as well as to undulate.Isolated axostyles can regenerate this movement in vitro when exposed to ATP in an appropriate ionic environment (2,29,40). The challenge is thus to explain how molecular ATPases that presumably reside in the cross-bridges between microtubules can affect the helical pitch of the overall lattice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have revealed that the cytoskeleton (i.e. axostyle and costa) of T. foetus remains rigid throughout the entirety of its swimming motion [24], as opposed to other trichomonads [25] and Giardia [14], in which body flexion can be observed. Because the cell body of T. foetus is shown to be rigid during swimming, the propulsive forces necessary for swimming must be the result of flagellar beating [24], making this microorganism ideally suited for the study of multi-flagellated propulsion.…”
Section: Introductionmentioning
confidence: 99%